A inserção de resorts no Litoral Sul da Paraíba: impactos socioambientais e sustentabilidade nas comunidades locais - Espínola, Rafaella Soares (2012)
The creation of artificial and delusional pleasure spaces of the so-called globalized civilization is producing, more and more, non-places like the resort-type enterprises. According to the principle that production of tourist places is bonded to the fetishization of destines, to fast consummation and the superficiality of the tourist-place relation, these enterprises are causing various environmental, social, economic and space impacts at the communities where they are located. Also considering that the insertion of the first resort at Paraíba s south littoral is relatively recent and the insertion of other enterprises like this is being polemically discussed, it tried to analyze the process of insertion of resorts at Paraíba s south littoral and its social and environmental impacts at the local communities, contributing, pari passu, with the discussion about the development aspect of tourism in the era of globalization. The research was based in concepts like time-space distantiation (GIDDENS,1995), ecological crisis (LEFF, 2009), sustainable development (LEFF, 2009; MENDONÇA, 1999; MOLINA E.,2001; MURPHY, 2001), vacation at ghettoes (KRIPPENDORF, 2000), among others. After the bibliographic review, a field research was realized starting from semi-structured interviews which counted with the participation of 14 representatives divided among the public and private sectors, and local communities. It opted to delimitate the field research to the city of Conde and surrounding communities, as well as the use of the quantitative and qualitative method of approach and the content analysis (BARDIN, 1997). The obtained results revealed the perceptions of the impacts due to the implantation of the first resort at the south littoral through the different social actors involved, demonstrating that the most part of the interviewed is total or partially in favor of this insertion, despite of the majority of the impacts cited is negative. It was seen that the conventional development tourism model, in which are inserted the megaprojects such as resorts, cannot contribute with sustainable development if it excludes the environmental, economic and social sustainability. Besides that, from the presentation of alternative models, it aimed to show that there is no way to promote development without fostering the local principle role and the insertion of the communities in the benefits of the activity.